Factors Influencing Biofortified Inpari IR Nutri Zinc Rice Production in Margatiga, East Lampung, Indonesia - Sri Indaryati; Nur Istiqomah; Novita Novita (Penerbit Goodwood, 2026)
Purpose: This study examines the production factors that determine the output of Inpari IR Nutri Zinc, a zinc-biofortified rice variety cultivated by smallholder farmers in Jayaguna and Negeri Tua villages, Margatiga Subdistrict, East Lampung Regency, Indonesia, and evaluates the extent to which these factors jointly explain variation in farm-level rice output. Methodology: A quantitative explanatory survey design was applied to fifteen farmers selected through simple random sampling from a population of 104 registered Inpari Nutri Zinc growers. Primary data on land area, seed quantity, urea and NPK Phonska fertilizer use, herbicide, fungicide, rodenticide, and insecticide application, and labor input were collected through structured interviews and analyzed using multiple linear regression in SPSS.Results: The regression model produced a coefficient of determination of 0.949 and an F-statistic of 90.012 at a significance level below 0.05, indicating that the nine production factors jointly explain 94.9% of the variance in rice output, with land area and urea fertilizer emerging as the most influential partial predictors.Conclusions: Land expansion and balanced fertilization remain the principal levers for raising Inpari Nutri Zinc productivity in the study area.Limitations: The small sample size and single-season crosssectional design constrain the generalizability of the coefficients. Contributions: The study offers empirically grounded guidance for extension planning and input allocation policy supporting biofortified rice diffusion in stunting-prone regions of Lampung Province.